Rebounds Are Structural Effects of Infrastructures and Markets - Wallenborn, Grégoire (Frontiers in Energy Research, 2018)
The promise of energy efficiency brings us to a lighter world, to a world that has less “losses” or dissipation. Energy efficiency is the realm of engineers, for whom machines can be described as quantitative inputs and outputs. The world of machines is supposed to be progressively “dematerialised” through various improvements in resource efficiency. Of course, we observe exactly the reverse: a multiplication of machines and growing resource exploitation. The possibility that improved efficiency leads to a world with more objects and more activities is called the Jevons paradox. In this paper, I explore this paradox through various academic disciplines (neoclassical economics, ecology, technology, sociology), taking seriously the way these disciplines not only analyse but also construct their proper worlds. The description of rebound effects is intimately linked to energy demand issues and to the understanding of how this demand is created and uncontrolled. A good description of rebound effects requires understanding how temporal and spatial aspects affect energy demand. The main argument of the paper is then the following: rebounds are systemic effects when saved energy is used elsewhere, at another time. Rebounds arise faster when infrastructures and markets enable energy to circulate, and when energy consumers are in competition. Rebounds participate then to the concentration of power. In conclusion, energy efficiency is a big business that actualises many materializations, machines and infrastructures, ever more high performance artifacts, always more productive.